Perioperative Acute Renal Failure at Chu-Kara - Mouzou, Essohanam (British Journal of Healthcare and Medical Research, 2025)
The aim of this study was to take stock of perioperative acute renal failure (ARF) in intensive care at Kara University Hospital. This was a retrospective, descriptive and analytical study of the records of patients with renal failure in the surgical intensive care unit of Kara University Hospital from 1 January 2021 to 31 December 2023. The parameters studied were: epidemiological, diagnostic, therapeutic and evolutionary aspects. Results: 94 cases of ARF were studied, with a frequency of 2.11%. The average age of the patients was 45.65 ± 20.02 years. The most common age group was elderly patients aged 60 and over. The sex ratio was 4.7. The majority of patients were rural (71.30%). The most common type of ARF was functional ARF (76%), followed by obstructive ARF (18%). Digestive surgery was the most common in 60.63% of cases, followed by uronephrological surgery (19.1%) and traumatological surgery (11.7%). General anaesthesia was most common, accounting for 85.10% of cases. The average length of stay in intensive care was 4.25 ±6.42 days. Complications accounted for 40.42% of cases, dominated by infections and hyperkalaemia. Management was associated with a high mortality rate of 31.91%. Conclusion: Perioperative ARF was the result of a combination of numerous factors related to the patient’s condition, delay in consultation, type of surgery, precarious haemodynamic events and perioperative infections. Management of perioperative acute renal failure is primarily preventive and aetiological.